Before Utopia : The Making of Thomas More's Mind - Dealy, Ross (Book collections on Project MUSE., 2020)
"This unique study considers the influences of Stoic critics on the evolution of Thomas More's thought. The author argues that More's engaement with Erasmus's work radicalized his understanding of Christianity and shaped the writing of Utopia."--